Risk Mitigation Analysis with the House of Risk (HOR) Method Approach in the Service Procurement Process - Zulfiadi, Zulfiadi; Arhami, Arhami; Fradinata, Edy (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Service procurement is a crucial part of supply chain operations, often susceptible to various risks that can disrupt business continuity. PT. Pupuk Iskandar Muda, a major fertilizer company in Indonesia, faces multiple risk events in its service procurement processes. This study aims to identify these risks and propose effective mitigation strategies using the House of Risk (HOR) method. The HOR model comprises two phases: risk identification and prioritization using Aggregate Risk Potential (ARP), followed by the development of mitigation strategies based on risk agent rankings. The results reveal 20 risk events and 19 associated risk agents, from which 10 were prioritized through Pareto analysis. Consequently, 11 mitigation strategies were formulated to address the root causes of these high-impact risks. The novelty of this research lies in its specific focus on risk mitigation in service procurement—an area often overlooked in supply chain literature, which typically emphasizes goods procurement. This study contributes to the development of more targeted and proactive risk management approaches, particularly for state-owned enterprises operating in complex, high-stakes industries.